Osimertinib for pretreated EGFR Thr790Met-positive advanced non-small-cell lung cancer (AURA2): a multicentre, open-label, single-arm, phase 2 study. Issue 12 (December 2016) - Goss, Glenwood; Tsai, Chun-Ming; Shepherd, Frances A; Bazhenova, Lyudmila; Lee, Jong Seok; Chang, Gee-Chen; Crino, Lucio; Satouchi, Miyako; Chu, Quincy; Hida, Toyoaki; Han, Ji-Youn; Juan, Oscar; et al.
Summary: Background: Osimertinib (AZD9291) is an oral, potent, irreversible EGFR tyrosine-kinase inhibitor selective for EGFR tyrosine-kinase inhibitor sensitising mutations, and the EGFR Thr790Met resistance mutation. We assessed the efficacy and safety of osimertinib in patients with EGFR Thr790Met-positive non-small-cell lung cancer (NSCLC), who had progressed after previous therapy with an approved EGFR tyrosine-kinase inhibitor. Methods: In this phase 2, open-label, single-arm study (AURA2), patients aged at least 18 years with centrally confirmed EGFR Thr790Met-positive mutations, locally advanced or metastatic (stage IIIB/IV) NSCLC who progressed on previous EGFR tyrosine-kinase inhibitor therapy received osimertinib 80 mg orally once daily; treatment could continue beyond progression if the investigator observed a clinical benefit. Patients with asymptomatic, stable CNS metastases not requiring steroids were allowed to enrol. The primary endpoint was the proportion of patients achieving an objective response by blinded independent central review using Response Evaluation Criteria in Solid Tumors, version 1.1. Response endpoints were assessed in the evaluable for response analysis set (ie, all patients who received at least one dose of osimertinib and had measurable disease at baseline according to blinded independent central review). Other endpoints and safety were assessed in all patients receiving at least one osimertinib dose (full analysis set). The study is ongoing and patients are still receiving treatment. This study is registered withClinicalTrials.gov, numberNCT02094261 . Findings: Between May 20, 2014, and Sept 12, 2014, 472 patients were screened, of whom 210 started osimertinib treatment between June 13, 2014, and Oct 27, 2014; 11 patients were excluded from the evaluable for response analysis set (n=199) due to absence of measurable disease at baseline by blinded independent central review. At data cutoff (Nov 1, 2015), 122 (58%) patients remained on treatment. The median duration of follow-up was 13·0 months (IQR 7·6–14·2). 140 (70%; 95% CI 64–77) of 199 patients achieved an objective response by blinded independent central review: confirmed complete responses were achieved in six (3%) patients and partial responses were achieved in 134 (67%) patients. The most common all-causality grade 3 and 4 adverse events were pulmonary embolism (seven [3%]), prolonged electrocardiogram QT (five [2%]), decreased neutrophil count (four [2%]), anaemia, dyspnoea, hyponatraemia, increased alanine aminotransferase, and thrombocytopenia (three [1%] each). Serious adverse events were reported in 52 (25%) patients, of which 11 (5%) were investigator assessed as possibly treatment-related to osimertinib. Seven deaths were due to adverse events; these were pneumonia (n=2), pneumonia aspiration (n=1), rectal haemorrhage (n=1), dyspnoea (n=1), failure to thrive (n=1), and interstitial lung disease (n=1). The only fatal event assessed as possibly treatment-related by the investigator was due to interstitial lung disease. Interpretation: Osimertinib showed clinical activity with manageable side-effects in patients with EGFR Thr790Met-positive NSCLC. Therefore, osimertinib could be a suitable treatment for patients with EGFR Thr790Met-positive disease who have progressed on an EGFR tyrosine-kinase inhibitor. Funding: AstraZeneca.